A Novel Approach to Overcome Adherence Property of Candida albicans - Saadaldin, Shama M J (Al-Nahrain Journal of Science, 2018)
The study is aimed to introduce a procedure that mimic the adherence of microorganisms to the plastic tube and to assess the suitable solution to irrigate these microorganisms. Candida albicans broth was inoculated into a 30 cm plastic tube for a certain period of time to allow the adherence of microorganism to the inner surface of tube. Tubes were irrigated with distilled water, tap water or different concentrations of sodium chloride (0.1-0.9%). The results showed that the percentage of Candida albicans which adhered to the inner surface of tube ranged between 0.27% and 30% of the initial inoculum. Tap water was superior than distilled water in removing the adherent Candida. Sodium chloride in concentrations 0.3%, 0.6% and 0.9% completely removed the attached Candida while the other concentrations showed inconsistent results. It concludes that irrigation with water or certain sodium chloride concentrations, which interfere with the fluidity of Candida albicans, is the simple and best method to eliminate the adherent microorganisms.